Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/acm2.12457
|View full text |Cite
|
Sign up to set email alerts
|

A technique for total skin electron therapy (TSET) of an anesthetized pediatric patient

Abstract: PurposeTotal skin electron therapy (TSET) is a technique to treat cutaneous lymphomas. While TSET is rarely required in pediatric patients, it poses particular problems for the delivery. It was the aim of the present work to develop a method to deliver TSET to young children requiring anesthetics during treatment.MethodsA customized cradle with a thin window base and Poly(methyl‐methacrylate) (PMMA) frame was built and the patient was treated in supine position. Two times six fields of 6 MeV electrons spaced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…13 TLD measurements have also been used to investigate newer TSET delivery techniques, such as the use of single electron fields (rather than paired electron fields), 12 the use of a platform to rotate the patient during beam delivery, 6,15 and the treatment of anaesthetised paediatric patients. 16 Guidi et al's review of the literature on in vivo dosimetry for TSET treatments also referred to several studies that used MOSFET dosimeters and radiochromic film, 10 as well as one study that reported diode measurements performed on 360 patients treated using electron beam radiation delivered to lesions at various anatomical sites. 17 The use of glass beads as alternative TLDs has also been reported, specifically for TSET dosimetry.…”
Section: Introductionmentioning
confidence: 99%
“…13 TLD measurements have also been used to investigate newer TSET delivery techniques, such as the use of single electron fields (rather than paired electron fields), 12 the use of a platform to rotate the patient during beam delivery, 6,15 and the treatment of anaesthetised paediatric patients. 16 Guidi et al's review of the literature on in vivo dosimetry for TSET treatments also referred to several studies that used MOSFET dosimeters and radiochromic film, 10 as well as one study that reported diode measurements performed on 360 patients treated using electron beam radiation delivered to lesions at various anatomical sites. 17 The use of glass beads as alternative TLDs has also been reported, specifically for TSET dosimetry.…”
Section: Introductionmentioning
confidence: 99%